Lasius meridionalis - Collingwood, C. A. (Zenodo, 1979)
39. Lasius meridionalis (Bondroit, 1919) Figs. 143-146. Formica meridionalis Bondroit, 1919:143. Lasius meridionalis (Bondroit); Pisarski, 1975. Lasius rabaudi Bondroit, sensu Wilson, 1955; Collingwood, 1963; Kutter, 1977. Worker: Clear yellow; pubescence on head rather dilute but close and very fine on gaster. Funiculus segments distinctly longer than wide; scapes and tibiae elliptical in cross section with thin front edge. Petiole sides straight to weakly convex, dorsal margin flat to slightly emarginate. Body and appendage hairs numerous. Length: 3.5-5 mm. Queen. Dark brownish black; general apparance shining with fine shallow microsculpture. Body pubescence dilute but close and very fine on gaster. Funiculus segments longer than wide; scapes and tibiae flattened with thin front edge. Scale straight sided, dorsal margin flat, occasionally weakly emarginate. Body and appendage hairs abundant. Head width 1.7-1.8 mm. Length: 7.0-8.0 mm. Male. Black; clypeus and frons distinctly shining with weak microsculpture. Pubescence sparse except on gaster where it is very fine and close. Frontal triangle, frontal furrow and mandibular teeth very distinct. Head at least as broad as alitrunk. Eyes with erect hairs, appendage and body hairs numerous. Cross vein m-cu often absent on fore-wings. Length: 4.0-4.5 mm. Distribution. Local; Denmark: EJ, NWJ, LFM, NEZ, B. - Sweden: Sk., BL, Hall., 01. and Dir. - Norway: VE (Stolpestad). - Finland: N (Korverhar). - Locally common in Southeast England and South Wales. - Range: Spain to Japan, Italy to Scandinavia. Biology. This species is characteristic of lowland sandy heath in North Europe. Nests are in the ground, often with low earth mounds and carton lined chambers. Flight period August. Fertilised queens start colonies through adoption by L. alienus. Males which have well toothed mandibles have been seen to pick up objects and to feed themselves. Note. I have followed Pisarski (1975) in separating this species from L. rabaudi. According to examples of all castes kindly sent by P. Werner from Czechoslovakia, L. rabaudi has much more dilute but longer pubescence and has the gaster brilliantly shining. Bourne (1973) synonymised L. rabaudi i. e. L. meridionalis, in England as L. umbratus. However, the different habits, flat appendages and rectangular scale in the queen, shining darker colour and fine sculpture in queen and male clearly distinguish the species from L. umbratus, although workers may be less easy to separate. : Published as part of Collingwood, C. A., 1979, The Formicidae (Hymenoptera) of Fennoscandia and Denmark., pp. 1-174 in Fauna Entomologica Scandinavica 8 on pages 102-104